The chemistry of textile fibres - Mather, R. R.; Wardman, R. H. (Cambridge : Royal Society of Chemistry, 2011)
Discussing the chemistry of textile fibres aimed at A level students and first year undergraduates, this title explains the characteristics required for polymers to be fibre-forming, the general physical properties needed from textile fibres, and the chemistry of important natural and synthetic fibres.--
The scope of textile fibres -- Cellulosic fibres -- Protein fibres -- Regenerated fibres -- Synthetic fibres -- High-performance fibres -- Other specialty fibres -- Enhancement of fibre performance by surface modification -- Fibre blends in textile fabrics.
Includes bibliographical references and index.
Keywords: Textile fibers; Textile chemistry; Textile chemistry; Textile fibers; Chimie textile; Textiles et tissus -- Recherche